2005
DOI: 10.1038/sj.bmt.1705138
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the use of anti-interleukin-6 monoclonal antibody with dexamethasone and 140 mg/m2 of melphalan in multiple myeloma: results of a pilot study including biological aspects

Abstract: Summary:Interleukin-6 (IL-6) is a major survival factor for multiple myeloma (MM) cells preventing apoptosis induced by dexamethasone (DEX) or chemotherapy. In all, 24 consecutive patients with MM in first-line therapy received DEX for 4 days, followed by melphalan (HDM: 140 mg/m 2 ) and autologous stem cell transplantation (ASCT). The anti-IL-6 monoclonal antibody (mAb) (B-E8) was given till haematological recovery, starting 1 day before DEX. Results were historically compared to MM patients treated with HDM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…This study confirms previous results showing elevated IL-6 plasma levels post-ASCT (21,23). This increase can be explained by the HDM-induced stress and also by the deletion of cells able to consume IL-6.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study confirms previous results showing elevated IL-6 plasma levels post-ASCT (21,23). This increase can be explained by the HDM-induced stress and also by the deletion of cells able to consume IL-6.…”
Section: Discussionsupporting
confidence: 82%
“…Given a blood volume of 5 l, the mean amount of circulating IL-6 is ∼39 ng. In patients with MM treated with HDM and ASCT and with anti-IL-6 mAb, we have calculated a median daily IL-6 production of 35 mg/d at day 9 post-ASCT (21). Thus, in the case of IL-6, the amount of circulating IL-6 is 1/1000 of the total amount of IL-6 produced per day.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is also an anti-apoptotic factor and a growth factor for myeloma cells. Antibodies to IL-6 have been in clinical trials for patients with myeloma, and although a pilot study indicated that blocking IL-6 may decrease the growth of myeloma cells in patients, 74 to-date, none of these trials have been exceptionally successful. These results suggest that targeting IL-6 by itself is not sufficient to inhibit bone destruction and myeloma tumor growth.…”
Section: Mechanisms Of Multiple Myeloma Bone Disease DL Galson Et Almentioning
confidence: 99%
“…40 Despite the early recognition of the importance of IL-6 for MM growth and survival, clinical studies aimed at blocking IL-6 in MM have not yet been translated into reliable long-term benefits. Ranging from the IL-6 inhibitor dexamethasone, 41,42 to specific IL-6 [43][44][45][46][47] or IL-6 receptor 48 blockade, therapeutic effects often vanish during prolonged treatment. In an environment devoid of IL-6, myeloma cells can adapt their receptor expression profile and switch to other gp130 cytokines.…”
mentioning
confidence: 99%